Approved Annual Plan 1996-97 Government of Haryana - Planning Commission (Planning Commission, 1997)
The Planning Commission, Govt, of India, have laid down following objectives/ priority areas to be pursued during the Eighth Plan :— Employment Generation, Containing population growth; Universalisation of elementary education, complete eradication of illiteracy among people in the age group of 15 to 35 years; Eradication of scavenging and provisions of safe drinking water, health care including immunisation to all villages; Growth and diversification of agriculture to achieve self-sufficiency in food and generation of surplus for export; Strengthening of infrastructural facilities i.e. energy, transport, communication and irrigation in order to support the process of growth in a sustainable manner.
Planning Department Government of Haryana